Quality changes in smoked Colisa fasciata from the markets of Manipur during storage - M., Karthikeyan; B., Dhar; B., Kakati; A., Hassan; S., Das (Fishery Technology, 2025)
The traditional smoking process adopted in the state of Manipur, is different from the smoking process adopted else where in the world. Fishes are not salted during the entire smoking process. Smoked fish Colisa fasciata obtained from the market were packed in low density polyethylene pouches (200 gauge thick) and evaluated for its quality during storage. The product had a moisture content of 9.77 %, which showed an increase (p<0.05) during storage whereas the crude protein and fat decreased (p<0.01) during storage. The total volatile base nitrogen and alpha amino nitrogen showed an increase (p<0.01) during storage indicating protein changes which is further confirmed by an increase in non protein nitrogen (p<0.05) and decrease in salt soluble nitrogen (p<0.05). The peroxide value and free fatty acid value increased during the storage period confirming fat degradation. The yeast andmould countswereminimal during storage but the visible fungal colonies increased during later periods of storage. The fresh smoked fish had a crispy texture, golden yellow colour and high smoky odour and the sensory quality showed a decline during storage. The product kept well up to 120 days under ambient storage conditions (30 Â± 20C).